POLA PENYEBARAN SPASIAL INVESTASI DI INDONESIA: SEBUAH PELAJARAN DARI MASA LALU - J. J. Sarungu (Muhammadiyah University Press, 2008)
Economic development theorists generally beliefs that investment mainly played an important role in economic growth. Based on that, one can easily to think that spatially disparity of economic growth mostly depends on spatially spread of investment. This work try to investigate the spatially spread pattern of investment in Indonesia in the past before the Asian financial and economic crisis occurred. In that time, the government development policy stressed not only on economic growth but also on reducing economic disparity included spatially. In the recent, the two kinds of economic development policies’ stressing are still continued by the government. Generally, the lessons from the past is that the spatially spread pattern of investment in Indonesia tended to still concentrated in the western Java island (in Jakarta and its surrounding) and also in the Sulawesi island. While in the other island, investment tended to spread.